2002
DOI: 10.1111/j.0004-8666.2002.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Who remains undelivered more than seven days after a single course of prenatal corticosteroids and gives birth at less than 34 weeks?

Abstract: Women who give birth very preterm, who remain undelivered more than seven days after prenatal corticosteroids, differ in the reasons for and timing of their first course from women who give birth within seven days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…Further, our in-depth side-study has reported no increase in physiologic risk factors for cardiovascular or metabolic disease at early school age. 39 Although our trial sample was representative of women at ongoing risk of preterm birth after an initial course of corticosteroids, 40 caution is required in generalizing our results to other treatment protocols or inclusion criteria. The recent Cochrane systematic review included 9 other randomized trials of repeat antenatal corticosteroid treatment, with varying number, frequency, and dose(s) of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our in-depth side-study has reported no increase in physiologic risk factors for cardiovascular or metabolic disease at early school age. 39 Although our trial sample was representative of women at ongoing risk of preterm birth after an initial course of corticosteroids, 40 caution is required in generalizing our results to other treatment protocols or inclusion criteria. The recent Cochrane systematic review included 9 other randomized trials of repeat antenatal corticosteroid treatment, with varying number, frequency, and dose(s) of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…McLaughlin and colleagues also looked at the accuracy of physicians in timing the administration of antenatal corticosteroids. 58 Overall, women treated before 28 weeks gestation were more likely to give birth more than seven days later than those treated after 28 weeks. It is difficult to say if that data reflects a quicker tendency by physicians to treat patients at risk of preterm birth at earlier gestations for fear of adverse neonatal outcomes, or an actual difference in likelihood to deliver between these groups.…”
Section: Timing Of Effectivenessmentioning
confidence: 93%
“…Unfortunately, obstetricians are limited in their ability to predict preterm delivery with such accuracy with approximately 50% of patients given an initial course of antenatal corticosteroids remaining undelivered 7–10 days later [66]. Women treated prior to 28 weeks gestation appear more likely to give birth more than seven days later than those treated after 28 weeks [67]. …”
Section: Repeated or Rescue Coursesmentioning
confidence: 99%